2014
DOI: 10.1530/eje-13-1009
|View full text |Cite
|
Sign up to set email alerts
|

THRA and DIO2 mutations are unlikely to be a common cause of increased bone mineral density in euthyroid post-menopausal women

Abstract: Objective: A new autosomal dominant disorder due to mutation of THRA, which encodes thyroid hormone receptor a, is characterised by severely delayed skeletal development but only slightly abnormal thyroid status. Adult mice with disrupted thyroid hormone action in bone due to a mutation of Thra or deletion of Dio2, encoding the type 2 deiodinase, have high bone mass and mineralisation despite essentially euthyroid status. No individuals with DIO2 mutations have been described and the adult phenotype of patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Full-length Gpa2 and Gpb5 cDNAs were amplified from total mouse brain RNA by RT-PCR using primers mGPA2F, GACTGTCCTTTGCAGATGCCC and murine GPA2R, AGCCCCGAG TTTGAGATACCC for Gpa2 and primers mGPB5F, AGCCTGGGGTACAAGTGTCAGC and mGPB5R, TGGAGCCAGTGGATGTGTGAG for Gpb5 . The Gpa2 and Gpb5 cDNAs were subcloned into pGEM-T Easy (Promega) and sequenced ( 36 ). GPA2 and GPB5 subunits were either coexpressed or expressed individually using the bicistronic vector pBudCE4.1 (Invitrogen): 1) Gpa2 was subcloned into the pBudCE4.1 using the Not I and Xho I sites resulting in expression of a His-V5-tagged GPA2 protein (GPA2-His-V5), 2) Gpb5 was subcloned into pBudCE4.1 using the Hin dIII and Bam HI sites resulting in expression of a hemagglutinin (HA)-tagged GPB5 protein (GPB5-HA), and 3) both Gpa2 and Gpb5 were subcloned into pBudCE4.1 (GPA2-His-V5+GPB5-HA).…”
Section: Methodsmentioning
confidence: 99%
“…Full-length Gpa2 and Gpb5 cDNAs were amplified from total mouse brain RNA by RT-PCR using primers mGPA2F, GACTGTCCTTTGCAGATGCCC and murine GPA2R, AGCCCCGAG TTTGAGATACCC for Gpa2 and primers mGPB5F, AGCCTGGGGTACAAGTGTCAGC and mGPB5R, TGGAGCCAGTGGATGTGTGAG for Gpb5 . The Gpa2 and Gpb5 cDNAs were subcloned into pGEM-T Easy (Promega) and sequenced ( 36 ). GPA2 and GPB5 subunits were either coexpressed or expressed individually using the bicistronic vector pBudCE4.1 (Invitrogen): 1) Gpa2 was subcloned into the pBudCE4.1 using the Not I and Xho I sites resulting in expression of a His-V5-tagged GPA2 protein (GPA2-His-V5), 2) Gpb5 was subcloned into pBudCE4.1 using the Hin dIII and Bam HI sites resulting in expression of a hemagglutinin (HA)-tagged GPB5 protein (GPB5-HA), and 3) both Gpa2 and Gpb5 were subcloned into pBudCE4.1 (GPA2-His-V5+GPB5-HA).…”
Section: Methodsmentioning
confidence: 99%
“…It should be highlighted that large collaborative studies even in selected populations at potentially higher risk of genetic mutations are required. For instance, a study of 100 individuals with high bone mass found no evidence of TRa or DIO1 mutations [36]. A large meta-analysis of genetic variants associated with thyroid function is currently underway and results are expected in the near future.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these in vivo experiments, studies have reported associations between higher than normal levels of free T3 and free T4 with reduced bone density and an increased risk of non-vertebral fractures. High free T4 and free T3 levels are associated with low bone density in the hip joint, while high free T4 levels are also associated with potential bone loss at the hip joint [16]. However, thyroid hormone has been shown to stimulate cells to secrete insulin-like growth factor I that further stimulates osteoblast progenitor cells and nally promotes the differentiation and proliferation of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%